Model Pengambilan Keputusan Investasi Berbasis Maqashid Syariah dan Metode Konvensional: Studi Komparatif pada Perbankan Syariah - Novi Riani (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2026)
Investment decision-making is a core function of banking institutions, serving as a key determinant of financial performance and sustainability. The conventional model focuses primarily on quantitative financial indicators, prioritizing profit maximization, short-term returns, and risk minimization through mathematical calculations such as Net Present Value (NPV) and Internal Rate of Return (IRR). Through a comparative analysis, this paper finds that while the conventional method offers objectivity and ease of measurement, it lacks ethical and social dimensions. Meanwhile, the Maqashid Syariah approach provides a more holistic decision-making model, though it requires standardized indicators to make qualitative assessments more measurable. The study concludes that an optimal decision-making process for Islamic banking can be achieved by combining the technical accuracy of conventional tools with the value-based guidance of Maqashid Syariah, resulting in investments that are both economically viable and socially responsible.